TPR-containing proteins control protein organization and homeostasis for the endoplasmic reticulum. (4th March 2019) - Graham, Jill B.; Canniff, Nathan P.; Hebert, Daniel N.
Abstract: The endoplasmic reticulum (ER) is a complex, multifunctional organelle comprised of a continuous membrane and lumen that is organized into a number of functional regions. It plays various roles including protein translocation, folding, quality control, secretion, calcium signaling, and lipid biogenesis. Cellular protein homeostasis is maintained by a complicated chaperone network, and the largest functional family within this network consists of proteins containing tetratricopeptide repeats (TPRs). TPRs are well-studied structural motifs that mediate intermolecular protein–protein interactions, supporting interactions with a wide range of ligands or substrates. Seven TPR-containing proteins have thus far been shown to localize to the ER and control protein organization and homeostasis within this multifunctional organelle. Here, we discuss the roles of these proteins in controlling ER processes and organization. The crucial roles that TPR-containing proteins play in the ER are highlighted by diseases or defects associated with their mutation or disruption.